Imprints that evoke absences at the ‘Salón del Nunca Más’ (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In Colombia, survivors of the armed conflict have created a wide repertoire of actions that challenge the State and society asa whole, demanding truth and justice. One of them is the Salón del Nunca Más. This article focusses the functions fulfilled by photographs and personal logs in this space according to their uses: create a memory of the armed conflict, symbolically repair the damage, show the agency of the mourners, facilitate the pedagogy of memory. Finally, it refers to the challenges involved in the existence of this memory initiative in a country that does not yet have adequate institutional instruments for its political and administrative management.
Keywords: Memory Iniciative; Armed Conflict; Colombia; Photography.